The present status and prospect of research on the de-ironing and bleaching technology of kaolin (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
The increase of degree of whiteness is an important method for Kaolin growth in value. In this paper, the occurrence of iron in kaolin was briefly described, and the methods of the de-ironing and bleaching technology of kaolin were introduced. The characteristics and the existing problems of all kinds of method were analyzed. Some new green environmental protection technology of the de-ironing and bleaching kaolin were introduced.